Assessment of Vibration and Noise Impacts of Drilling and Blasting Operations on Urban Structures: A Case Study of Zeberced Quarry, Abuja - Kayode A. IDOWU; Favour O. BENJAMIN; Emmanuel B. SAMANI (FUDMA Journal of Engineering and Technology, 2026)
This study assesses ground vibration and noise impacts from blasting operations at Zeberced Quarry, Abuja, on nearby urban structures within a 500–1000 m radius. Instrumental monitoring of eleven blast events recorded Peak Particle Velocity (PPV) using a portable seismograph and noise levels using a Class 1 precision sound level meter. Structural inspections were conducted on twenty buildings, complemented by a perception survey of thirty residents. Results show PPV values ranged from 2.50 mm/s at 500 m to 0.76 mm/s at 1000 m; significantly below the NESREA regulatory limit of 8 mm/s and USBM structural damage threshold of 50 mm/s, indicating minimal risk of direct structural failure. However, noise levels peaked at 68.20 dB(L) at 500 m, exceeding the NESREA daytime limit of 65 dB(L), though declining to 61.98 dB(L) at 1000 m. Resident surveys revealed 80% reported disturbance, including headaches, sleep disruption, and anxiety. The study concludes that while vibration-induced structural damage risk is low, noise pollution represents a critical environmental challenge requiring mitigation through acoustic barriers, controlled blasting schedules, and improved community notification systems.